Environmental Sustainability of Passenger Terminals in Airport Buildings (Journal of University of Babylon for Engineering Sciences, 2020)
The current era is witnessing more efforts aimed at building a better, sustainable and more environmentally friendly world, according to which the idea of converting the largest and most polluted central operational infrastructure into environmentally friendly facilities exists, and airports are among the most important of those structures that are a source of major global environmental pollution, whether it is due to the high emission of air pollution, disturbing noise, land use and energy consumption, also passenger terminals are the main and important pillar of airport design.This paper is concerned with the environmental dimension of sustainability in passenger terminal in airports. Other studies dealt with these issues from different environmental levels. However, they were selective in approach, and do not provide satisfactory comprehensive knowledge of these issues. So far, localized experiments have put forward theoretical plans and strategies concerned with transforming passenger terminals into sustainable buildings without putting them into action, with a global environmental evaluation system. In light of this, the problem of the paper is set to be the non-comprehensively of the available data/studies on environmental sustainability of passenger terminals in airports, and the most important levels related to achieving this in general, as well as on a local level, in specific. To achieve this goal, a descriptive analytical statistical methodology is adapted to assess previous studies to arrive at applying them in Arab countries, as well as globally and locally. The paper hypothesizes that passenger terminals would achieve basic levels of sustainable environmental handling, according to which results are analyzed and conclusion and recommendations are formed.